2016
DOI: 10.1007/s00792-016-0844-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth of high-elevation Cryptococcus sp. during extreme freeze–thaw cycles

Abstract: Soils above 6000 m.a.s.l. are among the most extreme environments on Earth, especially on high, dry volcanoes where soil temperatures cycle between -10 and 30 °C on a typical summer day. Previous studies have shown that such sites are dominated by yeast in the cryophilic Cryptococcus group, but it is unclear if they can actually grow (or are just surviving) under extreme freeze-thaw conditions. We carried out a series of experiments to determine if Cryptococcus could grow during freeze-thaw cycles similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…This grouping has been confirmed by numerous other studies including the recent work of Liu et al (2015a, 2015b) who showed that N. friedmannii, N. antarcticus, N. vishniacii and N. bhutanensis are in the albidus clade of the Filobasidiales based on a seven-gene (RPB1, RPB2, TEF1, CYTB, and 3 rDNA genes) phylogeny. Also relevant to the present study, Vimercati et al (2016) showed that the isolate from Volcán Llullaillaco (discussed below) forms a monophyletic clade with N. friedmannii based on long-read 18S environmental sequences (1739 bp, JX099190) from Llullaillaco (Lynch et al 2012). Likewise, the Naganishia isolate from Volcán Saírecabur studied by Pulschen et al (2015) showed 100% identity with N. friedmannii over a 599 bp region of the LSU rRNA gene.…”
Section: Phylogeny Of the Naganishia Cladementioning
confidence: 67%
See 4 more Smart Citations
“…This grouping has been confirmed by numerous other studies including the recent work of Liu et al (2015a, 2015b) who showed that N. friedmannii, N. antarcticus, N. vishniacii and N. bhutanensis are in the albidus clade of the Filobasidiales based on a seven-gene (RPB1, RPB2, TEF1, CYTB, and 3 rDNA genes) phylogeny. Also relevant to the present study, Vimercati et al (2016) showed that the isolate from Volcán Llullaillaco (discussed below) forms a monophyletic clade with N. friedmannii based on long-read 18S environmental sequences (1739 bp, JX099190) from Llullaillaco (Lynch et al 2012). Likewise, the Naganishia isolate from Volcán Saírecabur studied by Pulschen et al (2015) showed 100% identity with N. friedmannii over a 599 bp region of the LSU rRNA gene.…”
Section: Phylogeny Of the Naganishia Cladementioning
confidence: 67%
“…Concentrations of carbon and nitrogen are at or below detection limits (Table 1), even though deep sequencing of DNA in soils from 6030 m.a.s.l. indicates that there is foreign (Aeolian) plant DNA from lower elevations being deposited there (Vimercati et al 2016). In addition, these sites are all acidic, with pH values of 4.1–5.4 (Table 1), adding yet another dimension of stress to organisms living in these soils.…”
Section: The Environmental and Biogeochemical Settingmentioning
confidence: 99%
See 3 more Smart Citations